Overcoming the challenges of cancer drug resistance through bacterial-mediated therapy. Issue 4 (December 2019) - Zargar, Amin; Chang, Samantha; Kothari, Ankita; Snijders, Antoine M.; Mao, Jian-Hua; Wang, Jessica; Hernández, Amanda C.; Keasling, Jay D.; Bivona, Trever G.
Abstract: Despite tremendous efforts to fight cancer, it remains a major public health problem and a leading cause of death worldwide. With increased knowledge of cancer pathways and improved technological platforms, precision therapeutics that specifically target aberrant cancer pathways have improved patient outcomes. Nevertheless, a primary cause of unsuccessful cancer therapy remains cancer drug resistance. In this review, we summarize the broad classes of resistance to cancer therapy, particularly pharmacokinetics, the tumor microenvironment, and drug resistance mechanisms. Furthermore, we describe how bacterial-mediated cancer therapy, a bygone mode of treatment, has been revitalized by synthetic biology and is uniquely suited to address the primary resistance mechanisms that confound traditional therapies. Through genetic engineering, we discuss how bacteria can be potent anticancer agents given their tumor targeting potential, anti-tumor activity, safety, and coordinated delivery of anti-cancer drugs.